Transfer Pengetahuan Pemasaran Online Pada UMKM Makanan dan Minuman - Syamsudin; Aflit Nuryulia Praswati; Wafiatun Mukharomah; Muhammad Jabal Noor (Universitas Muhammadiyah Surakarta, 2021)
Micro Small Medium Entreprises (MSMEs) have contributed significantly to the regional economy over the years. UMKM are also one of the sectors that have the strength to withstand various economic shocks. This strength can be seen from the enthusiasm to continue producing so that employees can continue to work even though income has decreased. However, the Covid-19 Pandemic that is currently underway provides a different surprise. Various government policies, such as restricting outdoor activities and advice not to crowd, have made it difficult for MSMEs , especially the food and beverage sector, to offer their products. MSMEs must immediately innovate in marketing. When store operating time is limited in order to prevent the spread of the Covid-19 virus and consumers who are worried about shopping directly in stores, MSMEs can use online marketing so that products can be remembered and purchased by consumers. Universities have an obligation to participate in helping MSMEs to survive. Through community service activities, a team of lecturers and students at the Muhammadiyah University of Surakarta conducted a knowledge transfer program and online marketing skills at food and beverage MSMEs in Sragen Regency. This community service activity provides assistance in making product photos and brochures equipped with interesting captions, as well as online marketing videos for MSMEs in Sragen Regency.